PENGARUH INVESTASI DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN SEKTOR INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Arie Rahmawati Utami; Lena Farida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to examine the factors that affect the firm value that can be judged from its investment and profitability . Samples in this study were 7 food and beverage industry companies listed on the Indonesia Stock Exchange, which has published a financial report from 2010-2014.Methods of analysis in this study using simple regression analysis and multiple regression analysis. Test simple regression analysis is used to view the partial influence of the investment and profitability are included as independent variables in this study on the firm value.Test multiple regression analysis is used to view the simultaneous influence of the investment and profitability are included as independent variables in this study on the firm value.The results showed that variable investment and profitability have a positive influence on firm value.Key words: firm value, investment , profitabilit